Using Discovery Learning Method to Improve Students’ Learning Outcomes in the Topics of Matrix - Trisniwati, Retno; Utomo, Dwi Priyo; Khusna, Arif Hidayatul (FKIP Universitas Lampung, 2019)
The purpose of this study is to describe the implementation of discovery learning in a matrix material. This type of research is a classroom action research study consisting of two cycles with each cycle consisting of four stages: planning, implementation, observation, and reflection. The research subjects were 35 students in grade XI. The research instrument used was the observation sheet and test. Data analysis techniques consist of data reduction, data presentation, and conclusions. The results showed that there was an increase in student learning outcomes after learning discovery learning was applied. It was proven that in the first cycle there were 15 students (42.8%) who were complete and in the second cycle there were 29 students (82.8%) who were complete.Keywords: discovery learning, classroom action research, matrix. DOI: http://dx.doi.org/10.23960/jpmipa/v20i2.pp54-59